Implementation of Self-Assessment Techniques as Learners in Compulsory Indonesian Language Courses - Hilmi, Hubbi Saufan; Hapsari, Theresia Pinaka Ratna Ning (Universitas Muhammadiyah Malang, 2023)
College students need to be actively involved in their own learning. Active engagement in learning at the tertiary level requires self-awareness and self-direction. If students have high awareness and learning arrangements according to their preferences, then learning objectives can be achieved effectively and efficiently. This study aims to describe the implementation of students' self-assessment techniques as learners in MKWU Indonesian. This type of research is descriptive qualitative with literature study design. The data sources used are books and journals related to self-assessment evaluation techniques and Indonesian MKWU. Data in the form of information on self-assessment techniques in Indonesian MKWU was obtained by reading and noting methods. The data analysis technique used is an interactive analysis technique. The results of the study revealed that there were four self-assessment techniques for students as learners at MKWU Indonesian, namely focused autobiographical sketches, ranking or goal matching, checklists of interests/knowledge/skills, and self-assessment of learning methods/styles. Implementation of student self-assessment techniques as learning in the form of self-assessment instruments based on objectives or CPMK MKWU Indonesian. The four student self-assessment techniques can be used as a reference for MKWU Indonesian teachers to map students' abilities before learning takes place so that learning processes and outcomes are more effective.